An integrative framework of information as both objective and subjective. (June 2023) - Jarrahi, Mohammad Hossein; Ma, Yuanye; Goray, Cami
We present a model of information that integrates two competing perspectives of information by emulating the Chinese philosophy of yin-yang. The model embraces the two key dimensions of information that exist harmoniously: information as (1) objective and veridical representations in the world (information as object) and (2) socially constructed interpretations that are a result of contextual influences (information as subject). We argue that these two facets of information cocreate information as a unified system and complement one another through two processes, which we denote as forming and informing. While the information literature has historically treated these objective and subjective identities of information as incompatible, we argue that they are mutually relevant and that our understanding of one actually enhances our understanding of the other.